Synthesis and Spectral Studies of Ni(II) Dithiocarbamate Complexes and Their Use as Precursors for Nickel Sulphides Nanocrystals - Azile Nqombolo; Peter A. Ajibade (Journal of Chemistry)
Ni(II) dithiocarbamate complexes have been synthesized and characterized by UV-Vis, FTIR, and NMR spectroscopic techniques. Electronic spectra measurements indicate that the complexes are four-coordinate square planar geometry while the FTIR confirmed that the dithiocarbamates act as bidentate chelating ligands. The compounds were used as single source precursors and thermolysed at 220°C to prepare HDA-capped NiS nanocrystals which were characterized by absorption and photoluminescence (PL) spectra measurements, powder X-ray diffraction (PXRD), transmission electron microscopy (TEM), scanning electron microscopy (SEM), and energy dispersive spectroscopy (EDS). Absorption spectra studies showed that the synthesized NiS nanoparticles are blue-shifted relative to the bulk material and PL studies showed emission maxima that are red-shifted compared to the absorption band edges. The XRD patterns of the as-prepared NiS nanoparticles revealed cubic crystalline phases. TEM images showed spherical and close-to-spherical nanocrystals with the size in the range 12–38 nm for NiS1, 8–11 nm for NiS2, and 9–16 nm for NiS3. SEM images showed homogeneous surface morphology and EDS confirmed the presence of Ni and S and the formation of NiS nanoparticles.